Pengaruh Model Pembelajaran Problem Based Learning Berbantu Media Animasi terhadap Hasil Belajar Siswa pada Pelajaran Pendidikan Pancasila tentang Pancasila dalam Kehidupanku Kelas V SD Inpres Osmo - Kota, Matha Khristina; Ly, Petrus; Leu, Hendrika K. Sanggo (ARZUSIN, 2025)
This study aims to find out and improve the learning outcomes of students in Pancasila Education lessons through the Problem Based Learning Model with the help of animation media. This type of research is quantitative with the Pre-Experimental Design One Group. For the determination of the sample using the Sampling Purpose method, namely 21 students in class V of SD Inpres Osmok. Data collection in this study was using a test instrument, namely Pretest-Posttest, which was then analyzed with a t-test. The results of the analysis showed that tcounted 6.855 > ttable 2.085 with a significance value of 0.000 < 0.05 so that it can be concluded that there was a significant difference in the results of students' learning before being treated and after being treated using the Problem Based Learning Model assisted by animation media. This means that there is an influence of the Problem Based Learning model on the learning outcomes of students in grade V of SD Inpres Osmok.